Shifts in the swine nasal microbiota following Bordetella bronchiseptica challenge in a longitudinal study - Nielsen, Daniel W.; Hau, Samantha J.; Mou, Kathy T.; Alt, David P.; Brockmeier, Susan L. (Frontiers in Microbiology, 2023)
Bordetella bronchiseptica is a widespread, highly infectious bacterial pathogen that causes respiratory disease in swine and increases the severity of respiratory infections caused by other viral or bacterial pathogens. However, the impact of B. bronchiseptica infection on the swine respiratory microbiota has not been thoroughly investigated. Here, we aim to assess the influence of B. bronchiseptica infection on the community structure and abundance of members of the swine nasal microbiota. To do so, the nasal microbiota of a non-infected control group and a group infected with B. bronchiseptica (BB group) were characterized prior to B. bronchiseptica strain KM22 challenge (day 0) and on select days in the weeks following B. bronchiseptica challenge (days 1, 3, 7, 10, 14, 21, 36, and 42). B. bronchiseptica was cultured from nasal samples of the BB group to assess nasal colonization. The results showed that B. bronchiseptica colonization did not persistently affect the nasal bacterial diversity of either treatment group (alpha diversity). However, the bacterial community structures (beta diversity) of the two groups significantly diverged on day 7 when peak colonization levels of B. bronchiseptica were detected. This divergence continued through the last sampling time point. In addition, Pasteurella, Pasteurellaceae (unclassified), Mycoplasma, Actinobacillus, Streptococcus, Escherichia-Shigella, and Prevotellaceae (unclassified) showed increased abundances in the BB group relative to the control at various time points. This study revealed that B. bronchiseptica colonization can disturb the upper respiratory tract microbiota and further research is warranted to assess how these disturbances can impact susceptibility to secondary infections by other respiratory pathogens.